2022
DOI: 10.3390/curroncol29030154
|View full text |Cite
|
Sign up to set email alerts
|

Management of HER2-Positive Breast Cancer for a Young Patient with Visceral Crisis—The Adjuvant Role of Lifestyle Changes

Abstract: The safety profile and effectiveness of existing anti-HER2-targeted therapies have not been evaluated in patients with breast cancer and visceral crisis. We report the case of a 26-year-old woman who was diagnosed with advanced HER2-positive breast cancer and initially treated with curative intent therapy in a neoadjuvant setting, using Trastuzumab and Pertuzumab in combination with Docetaxel; her cancer recurred two years later, with liver metastases and pulmonary lymphangitic carcinomatosis, causing visceral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Currently, only case reports with weak levels of evidence have shown promising anti‐tumor effects for patients with visceral crises when combining HER2‐targeted therapy with chemotherapy. 27 Therefore, the combination of pyrotinib‐based therapies (including PyroC) needs to be further validated in dealing with a visceral crisis. Furthermore, we found that the efficacy of pyrotinib is not affected by the use of HER2‐targeted therapy as front‐line treatment including both neoadjuvant and adjuvant settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, only case reports with weak levels of evidence have shown promising anti‐tumor effects for patients with visceral crises when combining HER2‐targeted therapy with chemotherapy. 27 Therefore, the combination of pyrotinib‐based therapies (including PyroC) needs to be further validated in dealing with a visceral crisis. Furthermore, we found that the efficacy of pyrotinib is not affected by the use of HER2‐targeted therapy as front‐line treatment including both neoadjuvant and adjuvant settings.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with visceral crisis require rapidly effective treatment to address severe organ dysfunction, 26 but adequate assessment of randomized trials on these existing anti‐HER2‐targeted therapies' effectiveness has not yet been conducted. Currently, only case reports with weak levels of evidence have shown promising anti‐tumor effects for patients with visceral crises when combining HER2‐targeted therapy with chemotherapy 27 . Therefore, the combination of pyrotinib‐based therapies (including PyroC) needs to be further validated in dealing with a visceral crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Two case reports demonstrated the efficacy of tailored management for patients with lymphangitic carcinomatosis treated with eribulin (HR+/HER2- ABC) or paclitaxel, trastuzumab and pertuzumab in personalised doses (HER2+ ABC), achieving both positive symptom control and a partial radiological response [ 13 , 14 ].…”
Section: The Clinical Management Of Visceral Crisismentioning
confidence: 99%